1988
DOI: 10.1002/hep.1840080437
|View full text |Cite
|
Sign up to set email alerts
|

Fragmentation of gallstones using extracorporeal shock waves: An in Vitro study

Abstract: Eighty in vitro experiments were performed with single (n = 51) or multiple (n = 29) gallstones in order to find out which parameters are of prime importance for their disintegration by extracorporeal shock waves. A Dornier lithotripter and an upper limit of 1,500 discharges were employed. Although computed tomography density was significantly lower in cholesterol stones than in the noncholesterol stones (p less than 0.0001) and although the latter were significantly more often radiopaque (p less than 0.0001),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
1

Year Published

1989
1989
1994
1994

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(17 citation statements)
references
References 16 publications
3
13
1
Order By: Relevance
“…Confusing results have been obtained when the cholesterol content was related to fragmentation. Two negative (Schachler et al 1988;Schulte and Baron 1990) contrast to two positive reports (Zeman et al 1991;Nitsche et al 1993) which state however the contrary that stones with a high cholesterol need more or less shocks.…”
Section: Chemical Propertiescontrasting
confidence: 55%
See 1 more Smart Citation
“…Confusing results have been obtained when the cholesterol content was related to fragmentation. Two negative (Schachler et al 1988;Schulte and Baron 1990) contrast to two positive reports (Zeman et al 1991;Nitsche et al 1993) which state however the contrary that stones with a high cholesterol need more or less shocks.…”
Section: Chemical Propertiescontrasting
confidence: 55%
“…Two negative (Schachler et al 1988;Arends et al 1990) and a positive (Torres et al 1990) result were found. Impaction of a model stone or just covering of its surface diminished the fragmentation rate (Vakil et al 1991b;Parr et al 1992).…”
Section: Various Target Factorsmentioning
confidence: 90%
“…Clinical experience has shown that total stone volume and stone number are the major determinants of the fragmentation of gallstones [7,9,10]. Commercially available lithotripters can be used with different energy settings.…”
Section: Discussionmentioning
confidence: 99%
“…found necessary for fragmentation [10,12,13]. Beside the total stone volume the composition of the stone addition ally determines the success of fragmentation [14][15][16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…The most important factor is the total stone volume [10,11]. The clearance of the gallbladder after lithotripsy depends on the number and the size of the stones before lithotripsy [6].…”
Section: Discussionmentioning
confidence: 99%